Achieving Bright and Long-Lived Aqueous Room-Temperature Phosphorescence of Carbon Nitrogen Dots Through In Situ Host-Guest Binding - Li, Jie (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 Wiley‐VCH GmbH.